The challenging nature of primary T lymphocytes for transfection: Effect of protamine sulfate on the transfection efficiency of chemical transfection reagents - Ilnaz Rahimmanesh; Mehdi Totonchi; Hossein Khanahmad (Research in Pharmaceutical Sciences, 2020)
Background and purpose: The optimization of an effective non-viral gene delivery method for genetic manipulation of primary human T cells has been a major challenge in immunotherapy researches. Due to the poor transfection efficiency of conventional methods in T cells, there has been an effort to increase the transfection rate in these cells. Protamine is an FDA-approved compound with a documented safety profile that enhances DNA condensation for gene delivery. Experimental approach: In this study, the effect of protamine sulfate on the transfection efficiency of standard transfection reagents, was evaluated to transfect primary human T cells. In this regard, pre-condensation of DNA was applied using protamine, and the value of the zeta potential of DNA/protamine/cargo complexes was determined. T cells were transfected with DNA/protamine/cargo complexes. The transfection efficiency rate was evaluated by flow cytometry. Also, the green fluorescent protein expression level and cytotoxicity of each complex were identified using real-time polymerase chain reaction and MTT assay, respectively. Findings/Results: Our results demonstrated that protamine efficiently increases the positive charge of DNA/cargo complex without any cytotoxic effect on the primary human T cells. We observed that the transfection efficiency in DNA/protamine/ Lipofectamine® 2000 and DNA/protamine/TurboFect™ was 87.2% and 78.9%, respectively, while transfection of T cells by Lipofectamine® 2000 and TurboFect™ would not result in sufficient transfection. Conclusion and implications: Protamine sulfate enhanced the transfection rate of T cells; and could be a promising non-viral gene delivery method to achieve a safe, rapid, cost-effective, and efficient system which will be further applied in gene therapy and T cells manipulation methods.